Sistem Sistem Peringatan Dini Kebocoran Gas Pada Waterheater Menggunakan Sensor Mq-2 Berbasis IoT: Sistem Peringatan Dini Kebocoran Gas Pada Waterheater Menggunakan Sensor Mq-2 Berbasis IoT - Brian Hakim Pangestu; Zuly Budiarso (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
The cause of gas leakage accidents is usually due to a lack of immediate notification, especially since this is a gas that is invisible to the eye and very difficult to smell. Not only gas in the kitchen stove, but the use of gas is also found in warm water heaters, waterheaters for example. This research wants to provide solutions to these problems with leaks in the waterheater in the bathroom, because with such a small room, it is very dangerous if it spreads directly and is also close to a large fire during instant combustion in the waterheater engine. To solve this problem, this research uses methods including the analysis stage, the design stage, and the implementation stage. the results of this study are, if there is a gas leak in the waterheater heating machine, the Mq-2 sensor will detect and will turn on the red led indicator, then continue with the buzzer sound. Furthermore, notification via cellphone notification is also intended for people who are outside the room, which aims to pull out where the gas source comes from. Keywords— Gas leak, Waterheater, Sensor mq-2